Faktor Kriminogen dan Upaya Mengatasi Penyalahguna Narkoba di Kalangan Masyarakat - Teguh Suratman; Wika Yudha Shanty (Bhirawa Law Journal, 2022)
In fact, drugs are goods that are very useful for the benefit of many people's lives when used and used properly. However, in reality this is not the case, and not a few of these items are used inappropriately for their intended purpose or in other words, are misused and cause various negative aspects in the community. The purpose of this paper is to find out the criminogenic side of drug use that should not be carried out by the community, and to find out drug use among the community, which is actually not in harmony with social values, cultural aspects and negative factors in people's lives. The study in this paper contributes in overcoming the crime of drug abuse, in order to achieve the goal and to facilitate the understanding and implementation of handling drug problems using Pre-emptive, Preventive, and Repressive methods; and understand trends related to drugs, more specifically trying to contribute in solving the problem of drug abuse as part of the social pathology in people's lives.